Presentational nana constructions in Reunion Creole - Alina McLellan (Isogloss, 2024)
This paper discusses a cluster of related constructions in Reunion Creole involving nana ‘have’. Focusing on a presentational construction that is functionally equivalent to the il y a-cleft of French, I argue that a once bi-clausal cleft has developed into a monoclausal broad focus construction in Reunion Creole. I present a Role and Reference Grammar analysis of both the bi-clausal cleft and the monoclausal construction, and in the former, I explain how the cleft relative clause differs from restrictive relative clauses.